Inside Front Cover: Multi‐mode acquisition (MMA): An MS/MS acquisition strategy for maximizing selectivity, specificity and sensitivity of DIA product ion spectra. Issue 15 (August 2016) - Williams, Brad J.; Ciavarini, Steve J.; Devlin, Curt; Cohn, Steven M.; Xie, Rong; Vissers, Johannes P.C.; Martin, LeRoy B.; Caswell, Allen; Langridge, James I.; Geromanos, Scott J.
Abstract : DOI:10.1002/pmic.201500492 There is a fixed amount of m/z sufficient space in an MS/MS spectrum. The number of precursors that can accurately identified is a function of the pre‐fragmentation resolving powers ( m/z, chromatographic and drift). Precursor ion flux is not uniform across time, drift or m/z . This variability necessitates the width of the mass isolation window (MIW) to be dynamic. The described MMA workflow uses models and prior knowledge to dynamically set the MIW over the gradient elution. For more details, see the article by Brad J. Williams et al. on pages 2284–2301.